P345 The relationship between virulence of Candida albicans and environmental oxygen concentration. (20th September 2022) - Abe, Masahiro; Sadamoto, Sota; Shinohara, Takayuki; Nagamori, Akiko; Nagi, Minoru; Miyazaki, Yoshitsugu
Abstract: Poster session 3, September 23, 2022, 12:30 PM - 1:30 PM: Objectives: Candida species are known to colonize human skins and mucous membranes, and cause candidemia under various immunosuppressive conditions. Among these Candida species, C. albicans is reported to be the most frequently isolated species, and could colonize on skins, vaginas, gastrointestinal tracts, and medical devices. Environmental factors including oxygen concentration is thought to affect the capability of colonization and virulence of Candida species; however, most previous research was performed under aerobic condition, and few research focused on hypoxic conditions imitating inside the human bodies. Given these backgrounds, we performed murine experiments by culturing C. albicans under various oxygen conditions to evaluate the effect of environmental oxygen concentration on virulence. Through our studies, we aimed to clarify the actual behavior of C. albicans in the human body. Methods: In this study, female C57BL/6 mice, 7-8 weeks old, were used and injected via lateral tail vein to cause C. albicans dissemination. Mice were divided into 4 groups according to the pre-culture conditions: aerobic, microaerobic (5% oxygen concentration), microaerobic (1% oxygen concentration), and anaerobic. Under each oxygen condition, C. albicans was grown at 37°C for 2 days on yeast extract peptone dextrose (YPD) agar and then incubated in YPD broth for 16-24 h. After incubation, C. albicans was collected, washed, resuspended in sterile PBS, and injected into each mouse at ∼2.5 × 105 colony-forming units. In this study, one reference strain (SC5314) and one clinically isolated strain (from bloodstream infection) were used. These infected mice were euthanatized 2 or 4 days after injection, and organ (kidneys and brain) fungal burdens were evaluated. Results: The kidneys' fungal burdens were significantly higher in the microaerobic groups than those in the aerobic or anaerobic groups 2 and 4 days after injection. There were no significant differences between 5% oxygen concentration pre-cultured group and 1% oxygen concentration pre-cultured group. On gross examination, disseminated lesion formations were visible in the kidneys of the microaerobic groups. Similarly, the fungal burdens of brain were significantly higher in the microaerobically pre-cultured groups than in the aerobically or anaerobically pre-cultured groups. This tendency was similar for both the reference and clinically isolated strain. Conclusion: Our results indicated that C. albicans could become more virulent under hypoxia, especially under microaerobic conditions. We assumed that some virulence factors of C. albicans were elevated under microaerobic conditions. These results implicated that C. albicans could become more virulent under hypoxic conditions in human bodies. In the future, we will continue to evaluate factors related to this change in virulence and pathological analysis of infected organs.